Participatory Strategies for Fostering Environmental Awareness and Domestic Waste Management through Waste Segregation among Primary School - Hidayati Utami, Nurul; Kaspul; Prahatama Putra, Aminuddin; Ajizah, Aulia; Amintarti, Sri; Nurtamara, Luthfiana (Unram Journal of Community Service, 2025)
This community service project aimed to promote environmental awareness and sustainable waste management practices among primary school students at SDN Kuin Cerucuk V Banjarmasin. The program targeted students aged 8–12, a critical developmental stage for instilling environmentally responsible behaviour. Using a participatory approach, the activities included educational sessions, practical waste sorting exercises, and the installation of visual learning aids. Pre- and post-intervention assessments were conducted through direct observation and questionnaires to evaluate knowledge acquisition and behavioural changes. The results indicated a substantial improvement in students’ understanding of waste types and segregation practices. Prior to the intervention, 71.4% of students demonstrated limited knowledge, which shifted significantly post-intervention, with 71.4% achieving the highest knowledge category. Observable behavioural changes included consistent use of segregated waste bins and increased attentiveness to school cleanliness. The active involvement of teachers and school management contributed to the program’s success. However, sustainability challenges remain, including limited time for long-term mentoring, resource constraints among staff, and the absence of community-level waste infrastructure. Despite these obstacles, the project demonstrates that early environmental education, supported by collaboration and practical engagement, can effectively foster long-term behavioural change and lay the foundation for an environmentally conscious.